The Comparison of Demonstrative Learning Method and Computer Assisted Learning on Blood Pressure Measurement at STIKes Guna Bangsa Yogyakarta - Nur Yeti Syarifah (LPPM STIKES Guna Bangsa Yogyakarta, 2016)
Rationale: Learning methods in education demand a lecturer not only uses one learning method. It is hoped that the lecturer would deliver an effective and good learning process to his/her students so that the students would achieve better learning results.Therefore, the author is interested to conduct a study“The Comparison of Demonstrative Learning Method and Computer Assisted Learning on Blood Pressure Measurement Guna Bangsa Health College of Yogyakarta in 2012”.